2019
DOI: 10.1038/s41598-018-36651-2
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction prevents the development of airway hyperresponsiveness in mice on a high fat diet

Abstract: We have previously shown that high fat diet (HFD) for 2 weeks increases airway hyperresponsiveness (AHR) to methacholine challenge in C57BL/6J mice in association with an increase in IL-1β levels in lung tissue. We hypothesize that obesity increases AHR via the IL-1β mechanism, which can be prevented by caloric restriction and IL-1β blockade. In this study, we fed C57BL/6J mice for 8 weeks with several hypercaloric diets, including HFD, HFD supplemented with fructose, high trans-fat diet (HTFD) supplemented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Healthy individuals undergoing short-term CR have been shown to have reduced monocyte metabolic and inflammatory activity and a drastic decrease in circulating and organ monocyte numbers [55,56]. The recruitment of inflammatory cells in tissues and airway induced by intake of high fat or high caloric diet could be reversed by CR [57,58]. In this study, our results established that CR could reduce the levels of pulmonary and circulating inflammatory triggers.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Healthy individuals undergoing short-term CR have been shown to have reduced monocyte metabolic and inflammatory activity and a drastic decrease in circulating and organ monocyte numbers [55,56]. The recruitment of inflammatory cells in tissues and airway induced by intake of high fat or high caloric diet could be reversed by CR [57,58]. In this study, our results established that CR could reduce the levels of pulmonary and circulating inflammatory triggers.…”
Section: Discussionsupporting
confidence: 64%
“…Dietary intake could interact with xenobiotic response elements (XREs) to regulate the expression and activity of metabolizing enzymes, thus modifying the cellular response to xenobiotic stressors [60,61]. A line of evidence has demonstrated that CR acts as a modulator of XREs and up-regulation of the expression of enzymes involved in phase I, phase II metabolism and xenobiotic transport in mouse liver [29,58,62]. CR led to an increase in microsomal enzyme activity of cytochrome P450 (CYP450), modifying phase I metabolism of environmental toxicants [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, IL-33 is proposed to protect against the adipose tissue inflammation of obesity [40,41]. Increases in IL-1β and TNFα, have been proposed to contribute to the innate AHR of obesity [42][43][44]. Hence, we considered the possibility that ST2 deficiency augmented innate AHR in HFD-fed mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy individuals undergoing short-term CR have been shown to have reduced monocyte metabolic and in ammatory activity and a drastic decrease in circulating and organ monocyte numbers [59,60]. The recruitment of in ammatory cells in tissues and airway induced by intake of high fat or high caloric diet could be reversed by CR [61,62]. In this study, we establish that CR could reduce the levels of pulmonary and circulating in ammatory triggers.…”
Section: Discussionmentioning
confidence: 61%
“…Dietary intake could interact with xenobiotic response elements (XREs) to regulate the expression and activity of metabolizing enzymes, thus modifying the cellular response to xenobiotic stressors [64,65]. A line of evidence has demonstrated that CR acts as a modulator of XREs and up-regulation of the expression of enzymes involved in phase I, phase II metabolism and xenobiotic transport in mouse liver [30,62,66]. CR led to an increase in microsomal enzyme activity of cytochrome P450 (CYP450), modifying phase I metabolism of environmental toxicants [31,32].…”
Section: Discussionmentioning
confidence: 99%